Nodulação de cultivares de feijoeiro-comum influenciada por diferentes ciclos de crescimento - Andraus, Michel de Paula (2014)
Compared to other producing grain legumes, the common bean has short cycle, with high demand for nitrogen (N), which is the most mined and exported element by crops. N is a scarce element in tropical soils and the main sources, nitrate and ammonia, which may be available to the plant, are obtained from the decomposition of soil organic matter, mineral fertilization with nitrogen fertilizers and biological nitrogen fixation (BNF) held by pulses nodulating bacteria. This study aimed to identify characteristics related to FBN in common bean cultivars with different growth cycles, which reflect in higher productivity. The experiments were conducted under field conditions for two consecutive years (2012 and 2013) in the winter crop, in the experimental area of Embrapa Rice and Beans, in Santo Antônio de Goiás, Goiás. In both experiments installed in nearby areas were used as treatments 22 cultivars of common bean, two of the early growth cycle, eight semi-early growth cycle, ten normal cycle and two late- cycle treated with inoculant prepared in the Laboratory of Soil Microbiology, Embrapa Rice and Beans, compound by strains of Rhizobium tropici (SEMIA 4077, SEMIA 4080 and SEMIA 4088) recommended by the Ministry of Agriculture, Livestock and Food Supply as inoculants for the common bean cultivation. The design was randomized blocks . In the first year the collections were performed from V4 to R8 stage and were assessed at each stage the number, activity and dry weight of nodules, leaf area, dry weight and total nitrogen of aerial part (the R6 stage only), grain yield and its components (R9 stage) . In the second experiment the same evaluations were made, but only in R6 and R7 stages. Data were subjected to analysis of variance and the means compared by Skott-Knott test at 5% probability, graphs of Pearson correlation between variables were developed. The percentage of active nodules, leaf area, aerial part dry mass and total nitrogen were affected by cultivars. The number of nodules and dry weight of nodules were not affected. In stages of flowering and pod yield, nodule number, leaf area and dry weight of shoots were influenced by cultivars. The dry mass of nodules in flowering stage was influenced by the growth cycles and the regular and late cycles showed higher values. Grain yield was affected by cycles of cultivars and in the first experiment, early cultivars showed lower values than the other. Normal and late cycle cultivars arrived to total senescence of nodules on the phenological stage R7, while the early and semi-early cycles arrived to senescence of nodules in the R8 phase, however, there was minimal difference in days without active nodules between these.